Ascending Cholangitis due to Heavy Lifting - Bakkum, M.J. (Case Rep Gastroenterol, 2017)
Gallstone disease is the most common risk factor for cholangitis. In an anatomically normal bile duct system, cholangitis does not occur without the presence of stones. Endoscopic retrograde cholangiography with papillotomy and stone extraction is a well-established curative therapy for gallstones in the common bile duct. More important, papillotomy prevents recurrent episodes. The present case report describes a 73-year-old male with recurring cholangitis in a clear bile duct system after previous papillotomy. An etiology of duodenal reflux into the common bile duct due to heavy lifting is proposed.